Sustentabilidade e abastecimento alimentar nas metrópoles contemporâneas: o caso de São Paulo - Pereira, Sérgio Aparecido Rodrigues (2017)
The contemporary world presents challenges in many kind of activities. The population increasing in the metropolis indicates the necessity for a redirection in the decision making and presentation of solutions to the fulfillment of these demands. In Brazil, one sector to be rethought is food supply, whose wholesalers are obsolete in their design or urban setting and in their daily practices, today far from modern concepts of logistics, accessibility, sustainability and socio-environmental responsibility. With the purpose of discussing the food supply issue and proposing guidelines for the conceptual reformulation of these urban equipments, we researched the history of supply, neighborhood markets that had push to create urban centralities, several Central Wholesale and studied the case of the Companhia de Entrepostos e Armazéns Gerais de São Paulo - CEAGESP. We analyze its qualities and deficiencies and establish comparisons with other European Centers in order to explain and describe the differences pointed. In this work we present directives and parameters for the format of a Central adapted till the present, we discussed the urban plans to be implemented in Vila Leopoldina, in case the CEAGESP leaves there and we analyze the existing proposals of their relocation to another place, based on technical and urban guidelines and in order to minimize the impact to be caused by the Central Food in the region where it will be implemented.